ANALISIS PENGETAHUAN PENJAMAH MAKANAN TERKAIT HIGIENE SANITASI MAKANAN DI “WARUNG POJOK” UMI - Ramli, Rahmawati (Universitas Islam Negeri Alauddin Makassar, 2018)
Abstract Canteen is a special service that provides food and drink for students and staff located in places that are part of the campus building itself. But not only canteen, food stalls are there in the campus. Food stalls are usually cornered campus or have their own place outside the campus canteen area. This study was conducted with the aim to: analyze and assess the knowledge of food handlersThis research is phenomonological research using qualitative approach. The subjects of the study were food handlers, shop managers and environmental health care as expert informants. Data collection using focus group interviews and discussions for students. Researcher is the main instrument of research with assisted lecturer and interviewer. Data analysis techniques that represent data display, data reduction, and deduction of conclusions. The triangulation used to process the validity data is the source and way triangulation.The results of this study indicate that: Knowledge of hygiene achieves only attainment of consciousness (know and understand).